Effect of crosslink structure on mechanical properties, thermal stability and flame retardancy of natural flavonoid based epoxy resins. (5th January 2022) - Du, Yonggang; Zhao, Ge; Shi, Gonghui; Wang, Yiming; Li, Wei; Ren, Shitong
Graphical abstract: Highlights: Using renewable resources to prepare epoxy resin has important scientific value. Novel natural flavonoid based epoxy resins combines high impact strength and thermal stability. Cycloaddition is more effective than unilaterally increasing the number of epoxy groups. Rigid epoxy resin with high crosslink density is attractive. Abstract: Three novel bio-based epoxy resins were synthesized based on natural flavonoids (daidzain, naringenin and luteolin). Maleic anhydride was used as curing agent. The effect of crosslink structure on mechanical properties, thermal stability and flame retardancy of bio-based epoxy resins was investigated. The results showed that the mechanical properties of bio-based epoxy resins were significantly better than that of di-glycidyl ether of bisphenol A, but the flame retardancy of bio-based epoxy resins was not significantly improved compared with di-glycidyl ether of bisphenol A. The cycloaddition reaction of benzopyrone ring is conducive to the formation of high crosslink density. The mechanical properties and thermal stability of bio-based epoxy resins increased with increasing crosslink density. The impact strength and initial thermal degradation temperature of cured daidzein epoxy resin which with the highest crosslink density were 0.86 kJ/m 2 and 22 °C higher than that of di-glycidyl ether of bisphenol A, respectively. The glass transition temperature of cured daidzein epoxy resin was 184.4 °C.